Relationship between cognitive styles,levels of cognitive thinking and chemistry achievement among form four science students - Kamaruddin, Meor Ibrahim (Universiti Teknologi Malaysia, 2004)

(untitled)
This research is aimed to identify the cognitive styles, level of cognitive thinking and the chemistry achievement of form four science students in Johor Bahru. The research also investigated the relationship between the cognitive styles, the level of cognitive thinking and chemistry achievement. The Group Embedded Figures Test(GEFT), the Group Assessment of Logical Thinking (GALT) and the Chemistry Achievement Test (CAT) were used to determine the students cognitive styles, level of cognitive thinking and chemistry achievement respectively. A sample of 163 form four science students were involved in the research. The collected data were analyzed using the SPSS version 10.0 for Windows software. Results showed that most of the students were Field Dependent and they were at the concrete level of cognitive thinking. The analysis of CAT indicated that their achievement was low. There was a weak relationship between the students cognitive styles, the level of cognitive thinking and the chemistry achievement. This indicated that the chemistry achievement among the students was not very much influenced by the cognitive styles and the level cognitive thinking. Results also indicated that there was no significant difference between the cognitive styles, the level of cognitive thinking and the chemistry achievement. Several recommendations were made at the end of the report on ways educators could accommodate the diverse cognitive styles, and the level of cognitive thinking as well as ways to improve students achievement in chemistry.